1978
DOI: 10.3171/jns.1978.49.5.0635
|View full text |Cite
|
Sign up to set email alerts
|

Detachable balloon and calibrated-leak balloon techniques in the treatment of cerebral vascular lesions

Abstract: Of the cerebral vascular lesions that can be treated with intravascular detachable balloon techniques, carotid-cavernous sinus fistulas and vertebro-vertebral fistulas have the best results. The great advantage of this technique is that the cerebral blood flow can usually be preserved after the occlusion of the fistula. The authors report 17 postraumatic carotid-cavernous sinus fistulas successfully treated with preservation of the carotid blood flow in 12 cases. None of the patients died, and the morbidity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
3

Year Published

1981
1981
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(60 citation statements)
references
References 8 publications
0
54
0
3
Order By: Relevance
“…O esvaziamento de balões destacáveis acontece progressivamente entre três a quatro semanas após a embolização, permitindo neste intervalo a trombose e a resolução adequada da fístula 16 .…”
Section: Discussionunclassified
“…O esvaziamento de balões destacáveis acontece progressivamente entre três a quatro semanas após a embolização, permitindo neste intervalo a trombose e a resolução adequada da fístula 16 .…”
Section: Discussionunclassified
“…Ischemic complications after occlusion of the ICA occur in 5% to 22% of patients, despite a tolerant balloon occlusion test 3) . Despite the enormous progress made in endovascular techniques over the past few decades, detachable balloons remain the method of choice for the treatment of CCF with reported success rates of 75-88% in terms of preserving the patency of the parent ICA 4,12,13) . Although they are excellent therapeutic devices, there are some situations when detachable balloons cannot be used, if preservation of the parent artery is desired, particularly when the following are present : 1) a small orifice that does not allow the balloon passage, 2) a small cavernous sinus that causes the balloon to be herniated into the parent ICA, 3) sharp osseous fragments within the sinus that can cause rupture balloon on inflation, 4) a markedly enlarged cavernous sinus that cannot be completely filled by even multiple balloons, which leaves empty spaces that prevent complete occlusion and cure, and 5) transection of the cavernous ICA.…”
Section: Discussionmentioning
confidence: 99%
“…Ever since the use of balloons for the treatment of TCCFs was described by Debrun et al [13] and Serbinenko, [14] transarterial balloon embolization has been the criterion standard treatment for most patients with TCCF. Higashida et al [15] reported preservation of the parent artery in 88% of patients with TCCFs treated by using detachable balloons; other authors have described a need for parent artery occlusion in as many as 20% of cases [16,17].…”
Section: Review Of Endovascular Management Of Traumatic Carotid-cavermentioning
confidence: 99%